2011
DOI: 10.1515/cclm.2011.698
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative status in the lungs associated with tobacco smoke exposure

Abstract: TS exposure affected the balance between oxidative stress and antioxidant capacity of lungs. Preventing environmental TS exposure might decrease oxidative damage. Increased levels of 8-OHdG and SOD levels could be assessed as an early sign of airway damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 25 publications
4
34
0
2
Order By: Relevance
“…Similar results can be seen in GST activities by smoking (P=0.048, OR=2.57, 95% CI: 1.01-6.57) and alcohol (P=0.081, OR=2.19, 95% CI: 0.91-5.25) status (Table 3). Several studies indicated that the levels of MDA were higher in smokers (Bindu et al, 2004;Doruk et al, 2011). The levels of peroxidation products viz., MDA, GPx and GST were increased in all the tissues of alcohol administered and smoke-exposed rats (Chelchowska et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results can be seen in GST activities by smoking (P=0.048, OR=2.57, 95% CI: 1.01-6.57) and alcohol (P=0.081, OR=2.19, 95% CI: 0.91-5.25) status (Table 3). Several studies indicated that the levels of MDA were higher in smokers (Bindu et al, 2004;Doruk et al, 2011). The levels of peroxidation products viz., MDA, GPx and GST were increased in all the tissues of alcohol administered and smoke-exposed rats (Chelchowska et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of 8-isoprostane, prostaglandin E 2 , leukotriene B 4 [ 84 , 85 ], H 2 O 2 [ 70 ] and TNF-α [ 80 ] increased, whilst levels of IL-1 β [ 80 ], glutathione (an important antioxidant) [ 83 ] and pH [ 76 ] decreased minutes after cigarette smoking. Similarly, increased levels of oxidative markers, including MDA, 8-hydroxydeoxyguanosine, superoxide dismutase and glutathione peroxidise, were identified in the EBC of smokers compared with non-smokers [ 86 ]. Smokers should thus refrain from smoking at least 3 h and preferably overnight before EBC collection to minimise effects on mediator levels.…”
Section: Smokingmentioning
confidence: 99%
“…21 Some biomarkers are available for evaluating the oxidative stress in living organisms. 22 Some of these biomarkers are malondialdehyde, 8-oxo-7,8-dihydro-2Ј-deoxyguanosine, and coenzyme Q10. Each of these biomarkers is involved in oxidative processes.…”
Section: Introductionmentioning
confidence: 99%